From union to union nationalism, democracy and religion in Ireland - act of union to EU - Girvin, Brian (Gill & Macmillan, 2002)
"In its halcyon years, Irish nationalism was a model for the rest of the world. Why then were the practical achievements of early nationalist self-governments so paltry, collapsing in the economic and social disaster of the 1950s?" "Girvin identifies the following key points. First, religion was vital. The Old United Kingdom was a pan-Protestant state, which was why Protestant Wales and Scotland could find a place in it and Catholic Ireland could not. Second, Catholic nationalism could not accommodate Ulster Protestantism: it left the unstable sectarian cockpit of Northern Ireland to its own devices despite all the rhetoric about unity. Third, Irish nationalism ironically learned its core values of democracy and representative government from Westminster, a benign cultural legacy of the British presence. Fourth, nationalism was a political success but an economic failure. The yielding of some sovereignty in a EU context has been vital to Irish prosperity."--BOOK JACKET.